Effect of acute isotonic beetroot juice supplementation on maximal power in physically active individuals - Sim, Rachelle Yahn Yee (Nanyang Technological University, 2022)
Beetroot juice (BRJ) is a popular supplement reported to enhance sporting performance due to its high nitrate content. However, evidence is equivocal regarding the effect of BRJ on maximal power, warranting further research. New evidence suggests that isotonic beverages significantly increase salivary secretion, which may enhance the activation of nitrate. Hence, the combined effect of isotonic drinks and BRJ may induce greater enhancements in maximal power. This study primarily aims to investigate the differences between the effects of acute isotonic BRJ and normal BRJ supplementation on maximal power in physically active individuals through maximum countermovement jump with arm swing (CMJAS) and standing broad jump (SBJ), hypothesising a significant difference. Twenty-three individuals participated in a double-blind, randomised, crossover research. Participants completed two experimental trials conducted at least five days apart under either Condition BR or ISO-CB, in which they ingested two 285ml bottles of BRJ or isotonic BRJ respectively. A three-hour rest period was then administered before participants completed a five-minute warm-up followed by exercise testing, which included three CMJAS and SBJ, each separated by a 30-second break. The maximum CMJAS height and SBJ distance was retained for data analyses. No significant differences in the maximum CMJAS height (p=0.337, d=-0.205) and SBJ distance (p=0.828, d=0.046) across both conditions were reported. Hence, isotonic BRJ appears to add no significant benefit to maximal power. Future studies investigating the effect of isotonic BRJ on maximal power and other exercise performance measures should be conducted to form stronger conclusions. Keywords: beetroot, nitrate, isotonic, supplementation, power